Learning For Children With Special Needs: Analysis Of The Pai Teacher's Strategy - Mazrur Mazrur (At-Tarbiyat, 2023)
The learning process needs a special strategy, especially in this case about the practice of prayer in children with special needs (children with disabilities). Therefore, children with disabilities need direction and guidance from teachers so that they can understand the learning of prayer practices in accordance with the conditions they experience. For this reason, the purpose of this study is the learning strategy of PAI teachers in the practice of praying for children with disabilities. This type of research is qualitative with a descriptive approach. The subject of this study was a teacher of PAI subjects at SLBN Palangka Raya, while the informants were school principals and students with disabilities, data collection was carried out through observation, interviews, and documentation, the validity of the data was carried out using triangulation of sources and techniques, while data analysis was carried out by collecting data, reducing data, presenting, and drawing conclusions. The results showed that the learning strategy of Islamic Religious Education teachers in the practice of praying for children with disabilities at SLBN 1 Palangka Raya uses an individual learning strategy consisting of planning, including the preparation of RPP and PPI as well as learning resources. Meanwhile, the implementation, which includes teachers using individual strategies and is face to face, the methods used in learning are demonstrations, lectures, questions and answers, commands, and repetitions, while the media includes prayer videos, pictures about prayer practices, and prayer readings. While teacher evaluation through tests and non-tests.